Extrapituitary prolactin –1149 G/T promoter polymorphism in some rheumatoid arthritis patients - AL-Azzawie, Adnan F. (AL-Kindy College Medical Journal, 2015)
Background: Prolactin is a hormone, as well as a cytokine which is synthesized and secreted from the anterior pituitary gland and various extra pituitary sites including immune cells under control of a superdistal promoter that contains a single nucleotide polymorphism -1149 G/T. Rheumatoid Arthritis has been associated with increased serum prolactin levels.Objectives: To investigate the association of the extra pituitary -1149 G/T promoter polymorphism among Iraqi rheumatoid arthritis patients and prolactin levels.Methods: We tested 73 patients with rheumatoid arthritis and 40 healthy individuals. The DNA samples were genotyped using the Polymerase Chain Reaction-Restriction fragment Length Polymorphism method and the levels of prolactin serum were measured using Enzyme linked immunosorbent assay.Results: The parameters rheumatoid factor, C-reactive protein, erythrocyte sedimentation rate and serum prolactin concentrations of rheumatoid arthritis patients were significantly increased compared with healthy controls. The frequency of T allele and TT genotype was highest in control group compared with their frequency in rheumatoid arthritispatients, vice versa the G allele and GG genotype. There issignificant differences in prolactin levels in rheumatoid arthritis patients compared with healthy controls according to PRL-1149 G/T polymorphism. In rheumatoid arthritis patients, carriers of the GG, GT genotypes had higher prolactin levels in comparison to TT genotype but did not show any significant difference.Conclusions: There is a possible association between prolactin levels and rheumatoid arthritis. We found correlation between rheumatoid arthritis and prolactin -1149 G/T polymorphism. The prolactin -1149 G allele is a genetic marker for increased rheumatoid arthritis susceptibility in Iraqi population. In addition, influence of prolactin -1149 G/T polymorphism on prolactin levels